2021
DOI: 10.1017/jfm.2021.505
|View full text |Cite
|
Sign up to set email alerts
|

Statics and dynamics of a viscous ligament drawn out of a pure-liquid bath

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Unlike these alternatives, the ALE approach ensures an exact capture of the free surface, akin to the Lagrangian approach, while retaining the primary advantage of Eulerian methods that mesh elements are less prone to distortion. Consequently, it has gained widespread use in predicting the dynamics of free-surface flows across various phenomena such as droplet dynamics (Chubynsky et al 2020;Chakraborty, Chubynsky & Sprittles 2022), dynamics of a ligament (Wei et al 2021), jet breakup (Martínez-Calvo et al 2020b) and the instability of planar films (González et al 2016;Moreno-Boza, Martínez-Calvo & Sevilla 2020b). However, it is worth noting that this method is not suitable for scenarios where the topology of the domain might change, such as in cases involving fluids inside the film after rupture.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike these alternatives, the ALE approach ensures an exact capture of the free surface, akin to the Lagrangian approach, while retaining the primary advantage of Eulerian methods that mesh elements are less prone to distortion. Consequently, it has gained widespread use in predicting the dynamics of free-surface flows across various phenomena such as droplet dynamics (Chubynsky et al 2020;Chakraborty, Chubynsky & Sprittles 2022), dynamics of a ligament (Wei et al 2021), jet breakup (Martínez-Calvo et al 2020b) and the instability of planar films (González et al 2016;Moreno-Boza, Martínez-Calvo & Sevilla 2020b). However, it is worth noting that this method is not suitable for scenarios where the topology of the domain might change, such as in cases involving fluids inside the film after rupture.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%
“…2020; Chakraborty, Chubynsky & Sprittles 2022), dynamics of a ligament (Wei et al. 2021), jet breakup (Martínez-Calvo et al. 2020 b ) and the instability of planar films (González et al.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%
“…Unlike these alternatives, the ALE approach ensures an exact capture of the free surface, akin to the Lagrangian approach, while retaining the primary advantage of Eulerian methods that mesh elements are less prone to distortion. Consequently, it has gained widespread use in predicting the dynamics of free-surface flows across various phenomena such as droplet dynamics (Chubynsky et al 2020;Chakraborty et al 2022), dynamics of a ligament (Wei et al 2021), jet breakup (Martínez-Calvo et al 2020b) and the instability of planar films (González et al 2016;Moreno-Boza et al 2020b). However, it is worth noting that this method is not suitable for scenarios where the topology of the domain might change, such as in cases involving fluids inside the film after rupture.…”
Section: Direct Numerical Simulationsmentioning
confidence: 99%
“…[16][17][18] With the assumption of the bridge top attached to the edge of the probe, it was concluded that the remnant droplet rst increases and then decreases with stretching velocity. 19 Nevertheless, receding of the contact line was observed in dipping experiments and the results showed that the remnant volume remains constant at a high stretching velocity. 20 As a result, the contact line state has an important effect on the volume transfer of a conical liquid bridge.…”
Section: Introductionmentioning
confidence: 97%